Comparison of CRISPR-Cas9, CRISPR-Cas12f1, and CRISPR-Cas3 in eradicating resistance genes KPC-2 and IMP-4 - Jun Huang; Kanghui Ding; Jiahui Chen; Jiao Fan; Luyao Huang; Shaofu Qiu; Ligui Wang; Xinying Du; Chao Wang; Haifeng Pan; Zhengquan Yuan; Hongbo Liu; et al. (Microbiology Spectrum)
ABSTRACT Bacterial plasmid encoding antibiotic resistance could be eradicated by various CRISPR systems, such as CRISPR-Cas9, Cas12f1, and Cas3. However, the efficacy of these gene editing tools against bacterial resistance has not been systematically assessed and compared. This study eliminates carbapenem resistance genes KPC-2 and IMP-4 via CRISPR-Cas9, Cas12f1, and Cas3 systems, respectively. The eradication efficiency of the three CRISPR systems was evaluated. First, the target sites for the three CRISPR systems were designed within the regions 542–576 bp of the KPC-2 gene and 213–248 bp of the IMP-4 gene, respectively. The recombinant CRISPR plasmids were transformed into Escherichia coli carrying KPC-2 or IMP-4-encoding plasmid. Colony PCR of transformants showed that KPC-2 and IMP-4 were eradicated by the three different CRISPR systems, and the elimination efficacy was both 100.00%. The drug sensitivity test results showed that the resistant E. coli strain was resensitized to ampicillin. In addition, the three CRISPR plasmids could block the horizontal transfer of drug-resistant plasmids, with a blocking rate as high as 99%. Importantly, a qPCR assay was performed to analyze the copy number changes of drug-resistant plasmids in E. coli cells. The results indicated that CRISPR-Cas3 showed higher eradication efficiency than CRISPR-Cas9 and Cas12f1 systems.IMPORTANCEWith the continuous development and application of CRISPR-based resistance removal technologies, CRISPR-Cas9, Cas12f1, and Cas3 have gradually come into focus. However, it remains uncertain which system exhibits more potent efficacy in the removal of bacterial resistance. This study verifies that CRISPR-Cas9, Cas12f1, and Cas3 can eradicate the carbapenem-resistant genes KPC-2 and IMP-4 and restore the sensitivity of drug-resistant model bacteria to antibiotics. Among the three CRISPR systems, the CRISPR-Cas3 system showed the highest eradication efficiency. Although each system has its advantages and characteristics, our results provide guidance on the selection of the CRISPR system from the perspective of resistance gene removal efficiency, contributing to the further application of CRISPR-based bacterial resistance removal technologies.